How to Classify and Define Pituitary Tumors: Recent Advances and Current Controversies - Dai, Congxin; Kang, Jun; Liu, Xiaohai; Yao, Yong; Wang, Haijun; Wang, Renzhi (Frontiers in Endocrinology, 2021)
Pituitary tumors are very complex and heterogeneous with very wide range of proliferative and aggressive behaviors, and how to define and classify these tumors remains controversial. This review summarizes the epidemiology, the progress of the classification and definition of pituitary tumors, as well as the controversial issues. Although the new classification and definition of pituitary tumors has been modified, there are still some controversies. The terminology of pituitary neuroendocrine tumor (PitNET) was proposed by an International Pituitary Pathology, which could manifest unpredictable malignant behavior in small subset of aggressive pituitary adenomas (PAs). However, it may add new ambiguity to the origin of PAs, and more unnecessary anxiety and frustration to majority patients with benign PAs. The definition of aggressive PAs mainly relies on subjective judgment from clinical behavior, and lacks of objective biomarkers and unified diagnostic criteria. Whereas the term “refractory” could more accurately represent the characteristics of these tumors including clinical behavior, radiological features, pathologic findings, and clinical behavior. Moreover, the diagnostic criteria for refractory PAs are more strict, objective, and accurate than that for aggressive PAs. Early identify these patients through recognition and popularization the definition of refractory PAs will encourage the early use of aggressive therapeutic strategies for them.